Pendampingan Pembuatan Pupuk Kompos dari Enceng Gondok di Desa Kungkai Baru Kabupaten Seluma - Anton Feriady; Edi Efrita1; Fithri Mufriantie; Titi Darmi (JURNAL ABDIMAS SERAWAI, 2022)
This community service was carried out in Kungkai Baru Village, Air Periukan District, Seluma Regency. The material for this activity is the use of water hyacinth as a handicraft, where water hyacinth can be used for animal feed, handicrafts and compost which has a high economic value. The target of this service is the Segara Tani Women Farmers Group (KWT) in Kungkai Baru Village.The benefits of community service activities (1) Increase the knowledge and skills of members of the women's farmer group in Kungkai Baru Village in the use of water hyacinth (2) Increase the insight of the women members of the women's farmer group to open home industry business opportunities in making compost from water hyacinth.The results of this community service activity include (1) women members of women's groups in Kungkai Baru village are very enthusiastic in participating in all stages of this service activity (2) Increased knowledge and skills of women members of women's farmer groups in the use of water hyacinth (3) opening up the insights and thoughts of women members of farmer groups about the benefits of water hyacinth as a new business opportunity